Peningkatan Penguasaan Konsep Energi Melalui Implementasi Pendekatan Keterampilan Proses - Masrah, Masrah (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
The process skills approach is the management of learning activities by getting students actively involved. It is expected to be able to overcome problems that occur in students, namely difficulties in understanding the concept of learning science. This research is a class action research in two cycles. The study was conducted at SDN 004 / V Kuala Tungkal in class IV-B with a total of 32 students. To test the successful implementation of the process skills approach 10 questions were used for each cycle. Data obtained from test results, observations, and interviews with students. The results showed the average student score increased from 40.63 in pre-cycle to 50.63 in cycle I and 66.88 in cycle II. Based on interviews conducted, students feel better when learning with a process skills approach because they feel that’s more fun. Keywords: Conceptual understanding, energy, procces skills approach.